Comparative analysis of torque-adding wind energy conversion systems with a counter-rotating vs. conventional electric generator - Saulescu, Radu; Jaliu, Codruta; Neagoe, Mircea; Ciobanu, Daniela; Cretescu, Nadia (Frontiers in Energy Research, 2023)
The paper presents a comparative analysis on the steady-state behavior of two counter-rotating wind turbines with same components, where the generator can operate as counter-rotating (with both mobile rotor and stator -Case a) vs. conventional (with fixed stator -Case b) electric machine. These wind energy conversion systems (WECS) have also two coaxial counter-rotating wind rotors and a 1 degreeof-freedom (1-DOF) planetary speed increaser with two inputs, and one or two outputs for compatibility with the considered generator. The paper aims at highlighting the efficiency and energy performances of WECS with counter-rotating vs. conventional generator by investigating three functional scenarios (A, B and C) of the two WECS cases (a and b) under assumption of identical or different counter-rotating wind rotors. A generalized kinetostatic modeling algorithm is firstly proposed, starting from the general case of WECS with counter-rotating generator, which allows the establishment of analytical relations for speeds and torques at input and output shafts. Numerical simulations of the obtained closed-form model in each scenario highlighted the influence of the constructive parameters on WECS performances, as well as the energetic superiority of WECS with counter-rotating generator (Case a) vs. conventional generator (Case b): higher efficiency by 1.2% and more output power by 1% (Scenario A) to 5.5% (Scenario C).